PENGARUH ATRIBUT PRODUK TERHADAP LOYALITAS PELANGGAN PRODUK PRINTER INKJET EPSON - Tarmedi, Eded; Mardiawati, Nunung (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2010)
The development of printer machine nowadays is remakably marked by the latest innovation together with the product quality which continously improving with the advantage and new model as well as more interesting. This is the effect of global market which more competitive and the activity of the world trade more highly controlled by the demand and supply law. In Indonesia the printer industry competition, specially inkjet printer nearly most of them dominated by three big companies, namely Canon, Epson and Hewlett Packard where by this printer vendors, trying to apply various strategy to increasing its printer sale. There are so many kind of printers sold in Indonesia which arising the tough competition among the companies. Various kind of inovative products continously improved. In increasing the consumer loyalty, Epson company always develops its product atribute for interest of satisfying the consumer need. The consumer loyalty is very important to find out whether the consumers were satisfy with the products which was available in the Epson inkjet printer was very important known by the printer vendor.The aim of this research is to reveral the produt atribute description, consumer loyalty and how big was the influence of product atribute to the consumer loyalty of the product.Â  Research used Survey Eksplanatory technique, and the method used was survey. The research population was The Students Of Economic Education Department As The User of Epson Inkjet Printer of Indonesia Education University Jln. Setiabudhi Bandung, to reveal the influence of said variables used simple regresi analysis by the SPSS 11.5 programme help for windows.The results of the research showed that the product quality has the positive influence and adequate (0,634) on the consumer loyalty of the Epson inkjet printer product.. Recommendation which given to the product atribute was the Epson company should maintain and improve its quality product of various factors in order it can increase the satisfaction which in turn shall make the consumer become the loyal persons.